Corpo e Sagrado na idade eletrônica - Joachim, Sébastien (Ciência & Trópico, 2011)
RESUMO Tomando como referência diferentes áreas das ciências humanas, objetiva inquirir como o sagrado emerge no tempo atual. A partir da relação histórico-cultural do corpo e do sagrado, aprofunda a reflexão moderna sobre a mesma, considerando-a de três pontos de vista: o da psicanálise lacaniana, o da arte e o da sócio-antropologia. Deixa em aberto a questão de como as novas tecnologias tratam o imaginário do corpo e do sagrado, afirmando que “é imperativo promover uma ética-estética do distanciamento, uma outra regulagem de nossa demiurgia”. ABSTRACT Body and the Idea of What is Sacred in the Electronical Age. v. 24, n. 2, p. 319-332, jul./dez. 1996. Taking as reference approaches from different human sciences, aims to discuss the way through which things and ideas regarded as sacred emerges at the present. From the historical and cultural relationship between body and the idea of what should be regarded as sacred, examines the modern reflexion about that relationship, taking into consideration three points of view: the one of Lacan’s psychoanalysis, the one of art, and the one of socio-anthropology. Assumes as an open question the ways through which new technologies deals with the collective imagery about the body and what should be regarded as sacred, claiming that “it is imperative to foster an ethics/aesthetics of distancing, i. e., another ruling for our demiurgical experience.” RÉSUMÉ Corps et Sacré à l’ère électronique. v. 24, n. 2, p. 319-332, jul./dez. 1996. Prennant comme référence les différents champs des sciences humaines, l’article a pour objectif de discuter les manières, à travers lesquelles le sacré émerge dans le temps actuel. A partir de la relation historico-culturelle du corps et du sacré, il étudie plus profondement la réflexion moderne sur cette relation, en l’analysant sur trois points de vue: de la psychanalyse lacanienne, de l’art et de la socio-anthropologie. Il laisse ouverte la question: comment les nouvelles technologies traitent-elles l’imaginaire du corps et du sacré ? Et il affirme “qu’il faut absolument promouvoir une éthique-esthétique de l’éloignement, une autre régulation de notre démiurgie.